2018
DOI: 10.1089/neu.2017.5201
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Intrathecal Injection of the Conditioned Medium from Bone Marrow Stromal Cells on Spinal Cord Injury in Rats

Abstract: Bone marrow stromal cells (BMSCs) have been studied for the treatment of spinal cord injury (SCI). In previous studies, we showed that the transplantation of BMSCs, even though they disappeared from the host spinal cord within 1-3 weeks after transplantation, improved locomotor behaviors and promoted axonal regeneration. This result led to the hypothesis that BMSCs might release some neurotrophic factors effective for the treatment of SCI. The present study examined this by injecting the conditioned medium (CM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 32 publications
1
32
1
Order By: Relevance
“…Loss of differentiation potential, initiation of the host immune response, difficulties in delivery, and poor engraftment of transplanted cells are the major limitations of cell-based therapies [8,24]. Since the main effects of MSCs are likely mediated by paracrine mechanisms [25], we examined the effect of BMSC-CM as an alternative treatment for SCI. These experiments demonstrated that BMSC-CM can protect neuronal cells [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…Loss of differentiation potential, initiation of the host immune response, difficulties in delivery, and poor engraftment of transplanted cells are the major limitations of cell-based therapies [8,24]. Since the main effects of MSCs are likely mediated by paracrine mechanisms [25], we examined the effect of BMSC-CM as an alternative treatment for SCI. These experiments demonstrated that BMSC-CM can protect neuronal cells [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…Cell-based therapy may be suitable for the treatment of discrete lesions in SCI (Figs. 3 and 5) to provide the following: (1) trophic support, 59 (2) immunomodulation, 60,61 (3) angiogenesis, 35 (4) and generation of new CNS cells, 1,6 which may form functional relays (Fig. 6).…”
Section: Neuroregenerative and Neuroprotective Therapiesmentioning
confidence: 99%
“…70 Intrathecal injection of conditioned medium of MSCs into experimental SCI in rats was found to increase axonal regeneration and improve locomotor recovery 1-4 weeks after the treatment. 59 Stem cell-conditioned media contain several potentially regenerative factors, including insulin-like growth factor 1 (IGF-1), vascular endothelial growth factor (VEGF), transforming growth factor b1 (TGF-b1), and HGF. It has been reported that the use of such media are more effective than using individual factors or their combinations in enhancing the survival of neurons and growth of neurites.…”
Section: Reproduced Withmentioning
confidence: 99%
“…Considering all these secretions are contained in MSCs' culture medium, also known as conditioned medium (CM; Soleimanifar et al, 2018), it is a safer choice to use cell-free CM as a substitute for MSCT. Increasing publications have demonstrated the effectiveness of cell-free CM in ameliorating high glucose-induced degradation of ECM (Qi et al, 2018), inflammatory arthritis (Kay et al, 2017), wound healing (Amini et al, 2018), and spinal cord injury (Kanekiyo et al, 2018). Considering the regenerative property of CM, we therefore measured the potential of CM against OA in a rat model.…”
Section: Introductionmentioning
confidence: 99%